Transition from Technical Engineer to Managers and Leaders: Women’s Experience in Australia - Marinelli, Melissa Jane (Curtin University, 2017)
The Transition Continuum Model explains the ongoing and often unresolved nature of women engineers’ transitions to manager and leader. Qualitative methodology, informed by phenomenological and feminist perspectives, were used to explore this transition. Transitions occur over external, internal and temporal dimensions shaped by an interplaying triad of individual, relational and structural influences. The research shows that the multiple dimensions and influences must be considered together as a dynamic system.